Eksistensi Hidayah Sebagai Prinsip Epistemologi Islam: Analisis Tentang Hubungan Hidayah Dan Ilmu Pengetahuan - Luthfi (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2025)
The crisis of modern epistemology, rooted in the positivist-secular paradigm, has forcibly separated scientific facts from transcendental values, resulting in a loss of teleological orientation in science. This research aims to perform a philosophical reconstruction of the concept of hidayah, not merely as a theological dogma but as an active epistemological principle underlying the human cognitive process. Utilizing a qualitative-philosophicalmethod through library research, this study dissects authoritative classical and contemporary texts to uncover the organic relationship between hidayah and knowledge.The results indicate that hidayah functions as a